Model Strategic Marketing Education untuk Pertumbuhan Peserta Didik Baru di SMK Swasta: Analisis Strategis Berbasis SWOT - Eva Imelda Rahmah; Hapzi Ali (Indonesia Economic Journal, 2026)
The increasing intensity of competition among private vocational education institutions requires school leaders to design marketing architectures that are innovative, agile, and sustainable. This study proposes a Strategic Marketing Education Model by implementing a SWOT-based strategic analysis that systematically integrates Business Intelligence (BI), Digital Marketing, Cost-Friendly School Programs, and Perceived Service Quality. Employing a conceptual research design grounded in the Resource-Based View (RBV) theory and the framework of strategic educational marketing, this article examines how internal competencies and external dynamics determine institutional viability. The analytical synthesis demonstrates that data-driven decision-making, high-visibility digital communication, economically value-oriented programs, and superior service quality function as distinctive strategic resources. When integrated into a comprehensive institutional marketing architecture, these factors significantly influence parents’ and students’ school selection decisions, which in turn drive sustainable growth in new student enrollment. This study bridges a theoretical gap in the vocational education marketing literature and provides an applicable strategic roadmap for school management.